Deposition and Investigation of Hydrophobic Coatings; MATEC Web of Conferences; Vol. 37 : Smart Grids 2015 - Safonov A. Aleksey; Sulyaeva V. Veronika; Timoshenko N. Nikolay; Gatapova E. Elizaveta; Kabov O. A. Oleg Aleksandrovich; Kirichenko E. Ekaterina; Semenov A. Andrey (2015, 2015)
Title screen